Mucochytrium quahogii (=QPX) Is a Commensal, Opportunistic Pathogen of the Hard Clam (Mercenaria mercenaria): Evidence and Implications for QPX Disease Management - Sabrina Geraci-Yee; Jackie L. Collier; Bassem Allam (Journal of Fungi, 2022)
Mucochytrium quahogii, commonly known as QPX (Quahog Parasite Unknown), is the causative agent of QPX disease in hard clams (Mercenaria mercenaria), but poor understanding of the relationship between host and pathogen has hindered effective management. To address this gap in knowledge, we conducted a two-year study quantifying the distribution and abundance of M. quahogii in hard clam tissue, pallial fluid, and the environment. M. quahogii was broadly distributed in clams and the environment, in areas with and without a known history of QPX disease. M. quahogii in clams was not strongly related to M. quahogii in the environment. M. quahogii was always present in either the tissue or pallial fluid of each clam, with an inverse relationship between the abundance in the two anatomical locations. This study suggests that the sediment–water interface and clam pallial fluid are environmental reservoirs of M. quahogii and that there is a host-specific relationship between M. quahogii and the hard clam, supporting its classification as a commensal, opportunistic pathogen. There appears to be minimal risk of spreading QPX disease to naïve clam populations because M. quahogii is already present and does not appear to be causing disease in hard clam populations in locations unfavorable for pathogenesis.